Capillary electrophoresis mass spectrometry identifies new isomers of inositol pyrophosphates in mammalian tissues. Issue 3 (14th December 2022) - Qiu, Danye; Gu, Chunfang; Liu, Guizhen; Ritter, Kevin; Eisenbeis, Verena B.; Bittner, Tamara; Gruzdev, Artiom; Seidel, Lea; Bengsch, Bertram; Shears, Stephen B.; Jessen, Henning J.
Abstract : Capillary electrophoresis mass spectrometry demonstrates that the inositol pyrophosphates 2-PP-InsP5 and 4- or 6-PP-InsP5 exist in different mammalian tissues in addition to canonical isomers. Abstract : Technical challenges have to date prevented a complete profiling of the levels of myo -inositol phosphates (InsPs) and pyrophosphates (PP-InsPs) in mammalian tissues. Here, we have deployed capillary electrophoresis mass spectrometry to identify and record the levels of InsPs and PP-InsPs in several tissues obtained from wild type mice and a newly created PPIP5K2 knockout strain. We observe that the mouse colon harbours unusually high levels of InsPs and PP-InsPs. Additionally, the PP-InsP profile is considerably more complex than previously reported for animal cells: using chemically synthesized internal stable isotope references and high-resolution mass spectra, we characterize two new PP-InsP isomers as 4/6-PP-InsP5 and 2-PP-InsP5 . The latter has not previously been described in nature. The analysis of feces and the commercial mouse diet suggests that the latter is one potential source of noncanonical isomers in the colon. However, we also identify both molecules in the heart, indicating unknown synthesis pathways in mammals. We also demonstrate that the CE-MS method is sensitive enough to measure PP-InsPs from patient samples such as colon biopsies and peripheral blood mononuclear cells (PBMCs). Strikingly, PBMCs also contain 4/6-PP-InsP5 and 2-PP-InsP5 . In summary, our study substantially expands PP-InsP biology in mammals.